Pelestarian Tradisi Petirtaan Kanto Lampo sebagai Strategi Pengembangan Pariwisata Budaya Berkelanjutan di Desa Beng, Gianyar - Ni Gusti Ayu Nyoman Budiasih; Sutrisnawati, Ni Ketut; I Ketut Ardiasa; I Wayan Wijayasa; A. A. Sagung Ayu Srikandi Putri (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2025)
Kanto Lampo Petirtaan in Beng Village, Gianyar, is a sacred site that holds profound spiritual significance in Balinese Hindu tradition, serving as an important location for the melukat (spiritual purification) ritual and the collection of holy water (amertha), while simultaneously developing into a cultural tourism destination. This study aims to examine the role of the petirtaan in preserving local cultural traditions and its contribution to the development of sustainable cultural tourism. A descriptive qualitative approach was employed, involving observation, interviews, and literature review. The main theoretical used cultural heritage preservation theory, sustainable cultural tourism theory, and community-based tourism theory. The findings reveal that Petirtaan Kanto Lampo not only sustains spiritual values but also serves as a model of integrating cultural preservation with community-based management. Key strategies include the zoning of sacred and profane areas and educating visitors, emphasizing that strengthening local capacity and safeguarding sacred values are crucial for sustainable cultural tourism. Furthermore, the study demonstrates a synergy between cultural preservation and sustainable tourism development, despite challenges related to management, commercialization, and environmental pressure. The findings reaffirm the critical role of strengthening community-based tourism frameworks as a sustainable approach to mediating the tension between cultural sacredness and the shifting expectations of tourists in the modern era.